Structural Competencies: Re-Grounding Counseling Psychology in Antiracist and Decolonial Praxis. - Wilcox, Melanie M.; Pérez-Rojas, Andrés E.; Marks, Laura Reid; Reynolds, Amy L.; Suh, Han Na; Flores, Lisa Y.; McCubbin, Laurie D.; Wilkins-Yel, Kerrie G.; Miller, Matthew J. (Counseling Psychologist, 2024)
For counseling psychology to realize its commitments to uprooting anti-Black racism and white supremacy, we must shift from an individual to a structural frame of reference. We expand on prior calls to build upon the structural competencies approach that has been detailed in the medical literature and integrated into medical education. Whereas our existing "cultural" approaches orient us toward individual differences and characteristics, the structural competencies approach compels us to deeply understand, and ground our interventions in, how individual and community-level outcomes result from structural determinants of health, including and especially anti-Black racism and white supremacy. We further argue that we must take a structural competencies approach to all the work of counseling psychologists, not just psychotherapy. Using a hypothetical vignette, we briefly describe what such an approach might look like in practice. We provide recommendations for next steps in counseling psychology education and training.